Phase equilibria in the Bi2O3-CuO-Nb2O5 ternary system - Tan, Kar Ban; Chon, Mun Ping; Khaw, Chwin Chieh; Zainal, Zulkarnain; Yap, Taufiq Yun Hin; Chen, Soo Kien; Tan, Phei Yi (Elsevier, 2017)
A complete subsolidus ternary phase diagram of the Bi2O3-CuO-Nb2O5 (BCN) system was constructed. Careful firing control and phase analysis were applied to determine the phase assemblages and compatibilities over a wide range of temperatures, i.e. 700–925 °C. Phase-pure BCN pyrochlores were found to crystallise in cubic symmetry, space group Fd3m, No. 227 with lattice constants in the range of 10.4855 (5)<x<10.5321 (3). The mechanism of this limited subsolidus series could be represented by a general formula, Bi3.08−xCu1.84+2x/9Nb3.08+7x/9O14.16+6x/9 (0≤x≤0.36) wherein the reduction in Bi content was compensated by a proportion amount of copper and niobium together with non-stoichiometry in oxygen.